Exploring patient perceptions of repetitive transcranial magnetic stimulation as a treatment for chronic musculoskeletal pain: a qualitative study - Georgia Stillianesis; Rocco Cavaleri; Simon J Summers; Clarice Tang (BMJ Open, 2022)
Objective Repetitive transcranial magnetic stimulation (rTMS), a form of non-invasive brain stimulation, is a novel avenue for the management of chronic musculoskeletal pain. Despite evidence for the effectiveness of rTMS in chronic pain conditions, the clinical uptake of rTMS remains limited and little is known regarding patient perceptions of this therapeutic technique.Design Qualitative study using a phenomenological approach, reported in accordance with the Consolidated criteria for Reporting Qualitative research checklist.Setting Sydney, Australia.Participants Fifteen participants were recruited from the community and completed the study. All participants had a diagnosis of chronic musculoskeletal pain, a history of seeking treatment and no prior experience with rTMS.Methods and analysis All participants completed a semistructured interview to explore overall knowledge, preconceived concerns and attitudes regarding rTMS as a treatment for chronic musculoskeletal pain. The interviews were transcribed verbatim and analysed thematically.Results The key themes that influenced an individual’s hypothetical acceptance of rTMS for chronic pain management were (1) the individual’s initial impression of the equipment appearance, (2) the participant’s individual history and familiarity with technology, (3) the accessibility and availability of rTMS and (4) knowledge regarding pain physiology and rTMS.Conclusions This was the first qualitative study to explore the perception of rTMS as a treatment among people with chronic musculoskeletal pain. RTMS appears to be accepted as a treatment option among individuals with chronic musculoskeletal pain. Developing targeted strategies to address accessibility, funding support and medical endorsements may encourage use of rTMS in a clinical chronic pain setting.